If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7n + -4) + 4 = 12 + 7n Reorder the terms: 5(-4 + 7n) + 4 = 12 + 7n (-4 * 5 + 7n * 5) + 4 = 12 + 7n (-20 + 35n) + 4 = 12 + 7n Reorder the terms: -20 + 4 + 35n = 12 + 7n Combine like terms: -20 + 4 = -16 -16 + 35n = 12 + 7n Solving -16 + 35n = 12 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -16 + 35n + -7n = 12 + 7n + -7n Combine like terms: 35n + -7n = 28n -16 + 28n = 12 + 7n + -7n Combine like terms: 7n + -7n = 0 -16 + 28n = 12 + 0 -16 + 28n = 12 Add '16' to each side of the equation. -16 + 16 + 28n = 12 + 16 Combine like terms: -16 + 16 = 0 0 + 28n = 12 + 16 28n = 12 + 16 Combine like terms: 12 + 16 = 28 28n = 28 Divide each side by '28'. n = 1 Simplifying n = 1
| 2x+3z=2+5y | | 9n-8=-458 | | 9a-8=-260 | | 6n-5=271 | | 4p+8=-120 | | 27x^2-4=0 | | 3b+9=150 | | 50*50+140*140=x*x | | 2a=-38 | | 2x^2-12=-5+x | | x=1/2(80+60) | | 38-6n=4(-4n+3)-4 | | 4p=-164 | | x(x+4)+x(2+x)=x(2x)+12 | | -7a=-252 | | -t^2-13t=0 | | -39+6r=3+5(6+3r) | | x=1/2(40) | | -5j=250 | | 2(3x-2)-5(x-1)=1(3) | | -t^2-13=0 | | -8b=184 | | x=1/2(66-54) | | x=1/2(66+54) | | 1/4k=3/6k-1/4 | | 28-4n=-4n-7(n+3) | | (2x-1)(3x-1)=(x+1)(4x-2) | | 8x-18=39x+19 | | logx-1(4x-4)=2 | | t^2+13t=0 | | 4e^3x-2=244 | | 7(n+6)=98 |